2018
DOI: 10.1111/jpc.14345
|View full text |Cite
|
Sign up to set email alerts
|

Sirolimus in blue rubber bleb naevus syndrome: A systematic review

Abstract: The aim of this study is to review sirolimus as a treatment for blue rubber bleb naevus syndrome (BRBNS). A literature search of Medline, Embase, CINAHL, SCOPUS and Google Scholar was conducted for publications reporting treatment of patients with BRBNS with sirolimus. Of 46 articles identified, 17 studies reporting 23 patients met inclusion criteria. Sirolimus was well tolerated in all but one patient who required treatment cessation; 17/18 patients noted an improvement in gastrointestinal disease where this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 23 publications
1
28
0
Order By: Relevance
“…Minor or intermittent bleeding may be conservatively managed with iron supplementation or blood transfusions 14,15 . Recently, mTOR inhibitors have shown promising results in the management of complicated vascular anomalies 17,18 . Yuksekkaya et al reported the use of low‐dose sirolimus to successfully treat a child with BRBNS and recurrent GI bleeding 19 .…”
Section: Discussionmentioning
confidence: 99%
“…Minor or intermittent bleeding may be conservatively managed with iron supplementation or blood transfusions 14,15 . Recently, mTOR inhibitors have shown promising results in the management of complicated vascular anomalies 17,18 . Yuksekkaya et al reported the use of low‐dose sirolimus to successfully treat a child with BRBNS and recurrent GI bleeding 19 .…”
Section: Discussionmentioning
confidence: 99%
“…Medical management with sirolimus was initiated at the time of diagnosis to limit the frequency and severity of future gastrointestinal bleeds, which are almost ubiquitous in patients with BRBNS. 6 Sirolimus interferes with the function of mammalian target of rapamycin, inhibiting the mammalian target of rapamycin–mediated signal-transduction pathways, thereby resulting in the arrest of cell cycle in G1 phase in various cell types. 7 Aggressive surgical debulking of the large posterior trunk venous malformation was required to definitively treat the patient’s consumptive coagulopathy.…”
Section: Discussionmentioning
confidence: 99%
“…Anecdotal evidence suggests the superficial malformations are less responsive to sclerotherapy than typical VMs. Sirolimus appears to have a role in managing symptomatic gut lesions (Wang et al 2020;Wong et al 2019).…”
Section: Blue Rubber Bleb Naevus Syndrome (Brbns)mentioning
confidence: 99%